Metabolic syndrome as risk factor for left ventricular hypertrophy in children with chronic kidney disease - Drożdż, Monika; Moczulska, Anna; Rudziński, Andrzej; Drożdż, Dorota (Frontiers in Endocrinology, 2023)
Background: The metabolic syndrome (MS), a cluster of clinical and biochemical abnormalities including insulin resistance, dyslipidemia and hypertension, is often diagnosed in chronic kidney disease (CKD) children. Left ventricular hypertrophy (LVH) is a major target organ damage in hypertension and an important cardiovascular risk factor in CKD patients. We aimed to identify the most significant risk factors of LVH in children with CKD. Methods: Children with CKD stage 1-5 were enrolled in the study. MS was diagnosed according to De Ferranti (DF) as ≥3 from 5 criteria. Ambulatory blood pressure measurements (ABPM) and echocardiographic evaluation were performed. LVH was defined as ≥95th percentile of LV mass index related to height and age. Clinical and laboratory parameters included: serum albumin, Ca, HCT, cystatin C, creatinine, estimated glomerular filtration rate (eGFR) based on Schwartz formula, triglycerides, high-density lipoprotein (HDL), proteinuria, BMI standard deviation score (SDS), height SDS, waist circumference, ABPM data. Results: 71 children (28 girls/43 boys) with median age 14.05 (25%-75%:10.03-16.30) years and median eGFR 66.75 (32.76-92.32) ml/min/1.73m2 were evaluated. CKD stage 5 was diagnosed in 11 pts (15.5%). MS (DF) was diagnosed in 20 pts (28.2%). Glucose ≥ 110 mg/dL was present in 3 pts (4.2%); waist circumference ≥75th pc in 16 pts (22.5%); triglycerides ≥ 100 mg/dL in 35 pts (49.3%); HDL < 50mg/dL in 31 pts (43.7%) and BP ≥ 90th pc in 29 pts (40.8%), respectively. LVH was detected in 21 (29.6%) children. In univariate regression the strongest risk factor for LVH was CKD stage 5 (OR 4.9,p=0.0019) and low height SDS (OR 0.43,p=0.0009). In stepwise multiple logistic regression analysis (logit model) of the most important risk factors for LVH in CKD children, only three were statistically significant predictors: 1)MS diagnosis based on DF criteria (OR=24.11;95%CI 1.1-528.7; p=0.043;Chi2=8.38,p=0.0038); 2), high mean arterial pressure (MAP SDS) in ABPM (OR=2.812;95%CI 1.057-7.48;p=0.038;Chi2=5.91,p=0.015) and 3)low height SDS (OR=0.078;95%CI 0.013-0.486;p=0.006;Chi2=25.01,p<0.001). Conclusions: In children with chronic kidney disease LVH is associated with the cluster of multiple factors, among them the components of MS, hypertension, stage 5 CKD and growth deficit were the most significant.